AN CRITICAL VISUAL ANALYSIS OF GENDER STEREOTYPING IN THE INDONESIAN SECONDARY SCHOOL ENGLISH TEXTBOOK - Catur Wulandari; Hastowohadi Hastowohadi; Totok Hari Prasetiyo (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2024)
This research was intended to investigate the gender stereotype of thetextbook drawn from an English textbook series used in senior highschool employing a multimodal perspective and critical visual analysis.The study used a descriptive design because the writer wanted to describethe gender stereotype of the English textbook. The object of this study isthe Bahasa Inggris (edisi revisi 2017) textbook. The results of data analysisusing used three aspects of Kress and Van Leeuwen namelyrepresentational meaning, interactive meaning, and compositionalmeaning, the focus of the analysis was on images consisting of malecharacters and women use the theory of "critical visual analysis" and theconversation at the picture analyzed using critical discourse analysis(CDA). For the purpose of this study, there are five images selectedaccording to research on gender stereotypes and these images consist ofrandom male and female characters in images. The corollary of thiscritical image analysis was the teacher can know that the textbook is amedium that can trap students in interpreting images and selection ofimages in language textbooks must be more careful.